A clinical, microbiological and immunological comparison between subgingival irrigation with Dentol(™) and chlorhexidine in advanced periodontitis - Shahab, Azadeh (Termedia Publishing House, 2011)

(untitled)
INTRODUCTION: The purpose of this study was to compare the clinical, microbiological and immunological effects of subgingival irrigation with Dentol(™) and 0.2% chlorhexidine in human advanced periodontitis. MATERIAL AND METHODS: Twenty cases of advanced periodontitis patients were randomly treated either with Dentol(™) (as test) or 0.2% chlorhexidine (as control) every other day for 29 days after primary scaling, root planing and oral hygiene instruction. Pocket depth (PD), bleeding on probing (BOP) and plaque index (PI) were considered as clinical parameters. Total counts of aerobic and anaerobic bacteria were measured in subgingival plaque. At the end, concentrations of TNF-α and IL-1β in gingival crevicular fluid were measured as inflammatory markers. RESULTS: PD and BOP decreased in both groups on the 29(th) day and two weeks afterward. PI did not show any statistical difference either within or among groups (p > 0.05). Results indicate that both chlorhexidine and Dentol(™) diminished total count of subgingival anaerobic bacteria significantly (p < 0.05). Total count of subgingival aerobic bacteria increased in both groups, but the differences between the two groups were statistically significant in favour of Dentol(™) (p < 0.05). The level of IL-1β in the crevicular fluid was reduced in both groups but it was more significant in the test group (p < 0.05). The TNF-a level decreased in both groups but the statistical difference between the two groups was negligible (p > 0.05). CONCLUSIONS: Subgingivally irrigation with Dentol(™), containing 0.02% carvacrol, every other day for 29 days is equally or more effective than 0.2% chlorhexidine in reducing clinical and immunological inflammatory indices.